Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to understand the derivation here

I understand how first, second total differentials are derived. I do not understand how they are plugged into a form that is compatible with the single variable Taylor Series, which is

$f(x) = f(a) + f'(a)(x-a) + \frac{1}{2!}f''(a) (x-a)^2 + ...$

The coefficients of multivariate expansion are exactly the same as the single variable version. Sure given the total differential, $(x-a)$ is substituted for $dx$, $(y-b)$ for $dy$, but it's not shown why, or how the rest of $f(x,y)$ expansion should mirror the single variable form based on the total differential. Expansion for $f(x,y)$ is below

$f(x,y) = f(a,b) + \bigg[(x-a)\frac{\partial}{\partial x} + (y-b)\frac{\partial}{\partial x}\bigg]f + \frac{1}{2!} \bigg[(x-a)\frac{\partial}{\partial x} + (y-b)\frac{\partial}{\partial x}\bigg]^2 f + ... $

If you know a better 2D Taylor Series derivation, that would be welcome as well.


share|cite|improve this question
This is not a rigorous proof: Suppose that one can write $f(x,y)=f(a,b)+A(x-a)+B(y-b)+C(x-a)^2+D(x-a)(y-b)+E(y-b)^2+\cdots$, how can the values $A, B, C, D, E, \dots$ be determined? – pharmine Sep 27 '11 at 11:08
I think I came across a similar idea here pg 7. Thanks. – BB_ML Sep 27 '11 at 11:26
up vote 4 down vote accepted

So we want to express $f(a+u,b+v)$ in terms of $f(a,b)$, the increment $(u,v)$ and the partial derivatives of $f$ at $(a,b)$. To this end we look at the auxiliary function $$\phi(t):=f(a+t u, b+t v)\qquad(0\leq t\leq 1)\ .$$ By the one-variable Taylor theorem we have $$f(a+u,b+v)=\phi(1)=\sum_{r=0}^n{1\over r!}\phi^{(r)}(0)+{\rm error\ term}\ .\qquad(*)$$ Therefore we have to compute the successive derivatives of $\phi$ at $t=0$.

Obviously $$\phi^{(0)}(t)=\phi(t)=f(a+tu,b+tv)$$ and therefore $\phi^{(0)}(0)=f(a,b)$. To compute $\phi'(t)$ we need the chain rule: $$\phi'(t)={d\over dt}\phi(t)={d\over dt}f(a+t u,b+ t v)=f_1(a+t u,b+ tv)u+f_2(a+ tu, b+ tv) v\ ,$$ whence $\phi'(0)=f_1(a,b)u+f_2(a,b)v$. Proceeding in this manner we get $$\eqalign{\phi''(t)&={d\over dt}\bigl(f_1(a+t u,b+ tv)u+f_2(a+ tu, b+ tv) v\bigr) \cr &=f_{11}(a+tu,b+tv)u^2+2f_{12}(a+tu,b+tv) uv +f_{22}(a+tu,b+tv)v^2\cr}$$ and therefore $\phi''(0)=f_{11}(a,b)u^2 + 2f_{12}(a,b)uv+f_{22}(a,b) v^2\ .$ And so on for the higher derivatives of $\phi$. The values $\phi(0)$, $\phi'(0)$, $\phi''(0)$, $\ldots$ so obtained have to be plugged into the equation $(*)$

Of course all of this could be written up more elegantly using vector notation.

share|cite|improve this answer
Hi Christian, with $1$ in $f_1$ did you mean the first block of variables, which are $a+tu$? – BB_ML Sep 28 '11 at 6:01
Similar idea – BB_ML Sep 28 '11 at 6:02
@user6786: $f$ is a function of two real inputs, whatever their name. By $f_1$ I mean the partial derivative with respect to the first input. It seemed strange to write $f_x$ when there is nowhere an $x$ in the argument. – Christian Blatter Sep 29 '11 at 13:26

If you are looking for a physical intuition behind multivariate Taylor series, remember that $ T_x = \partial_x$ is the generator of translations, as for suitable class of functions: $$ (T_x f)(x) = \lim_{\epsilon \to 0} \frac{ f(x+\epsilon) - f(x)}{\epsilon} $$ Thus $\mathcal{T}_a = \mathrm{e}^{a T_x}$ is the operator of translation by $a$: $$ (\mathcal{T}_a f)(x) = f(x+a) $$ Writing defining series of exponential give univariate Taylor expansion: $$ f(x+a) = (1 + a T_x + \frac{a^2}{2!} T_x \circ T_x + \ldots ) \circ f(x) $$ Taking this to mulrivariate, the translation by vector $\vec{u}$ becomes $$ \mathcal{T}_\vec{u} = \exp( \sum_{i=1}^n u_i T_{x_i} ) = \circ_{i=1}^n \mathcal{T}_{u_i} $$ You can now develop each univariate translation operator into a series, giving the multivariate Taylor expansion formula or, alternatively, you could expand the combined exponential:

$$ f(\vec{x} + \vec{u}) = \sum_{n=0}^\infty \frac{1}{n!} \left( \langle \vec{u}, \mathcal{T}_{\vec{x}} \rangle \right)^n \circ f(\vec{x}) $$

Hope this helps.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.